The Effect Of Perception Of Training Results And Work Motivation On Frontliners Employee Performance At PT Mass Rapid Transit Jakarta (PERSERODA) - Kurniawan, Sandy Ricky; Sukiman, Sukiman; Priyono, Sigit (SEAN Institute, 2024)
This study aims to analyze the influence of the perception of training results and work motivation on the perfomance of fronliner employees at PT Mass Rapid Transit Jakarta (Perseroda). The research method used is a quantitative method. The sampling method employeed is non-probability sampling, with the accidental sampling technique. To determine the sample size, the author used the Slovin formula. The sample size taken was 98 respondents. The measurement tool used was a questionnaire. The analysis technique used was multiple linear regression analysis. The research results show that partially, the variable of perception of training results does not have a positive and significant effect on the perfomance of frontliner employees at PT Mass Rapid Transit Jakarta (Perseroda). However, the variable of work motivation partially has a significant and positive effect on the perfomance of frontliner employees at PT Mass Rapid Transit Jakarta (Perseroda). Simultaneously, the variables of perception of training results and work motivation significantly affect the perfomance of frontliner employees at PT Mass Rapid Transit Jakarta (Perseroda).